Comparative analysis of grid-connected bifacial and standard mono-facial photovoltaic solar systems - Nor Hidayah Abdul Kahar; Nurul Hanis Azhan; Ibrahim Alhamrouni; Muhammad Nubli Zulkifli; Tole Sutikno; Awang Jusoh (Institute of Advanced Engineering and Science, 2023)
This paper describes the design of a solar photovoltaic (PV) system using simulation of PVsyst software. This work involves the simulation of bifacial and mono-facial PV solar in a large-scale solar system. For a bifacial system, the yearly total energy to the grid is 1699.6 MWh, with an average of 4.57 kWh/kWp/day. For a mono-facial system, the total energy to the grid over the year is 1645.3 MWh, with an average of 4.05 kWh/kWp/day. The average collection losses obtained for bifacial and mono-facial modules were 0.33 kWh/kWp/day and 0.82 kWh/kWp/day, respectively, with system losses of 0.15 kWh/kWp/day (bifacial) and 0.18 kWh/kWp/day (mono-facial). The average performance ratio for bifacial and mono-facial was 0.904 and 0.801, respectively. The bifacial PV system was able to generate profit in terms of Return on investment (ROI), around 357%, and reach a breakeven around 7 years. The payback period for a mono-facial PV system was around 8.1 years, with an ROI of 290.4%. This work mainly focuses on a comparative analysis of bifacial and mono-facial photovoltaics, emphasizing the effectiveness and the implementation suitability of bifacial photovoltaics over mono-facial PV solar systems.